1991
DOI: 10.1055/s-0038-1647454
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor Released from Leukemic Cells

Abstract: SummaryUsing clotting assay and radioimmunoassay (RIA), tissue factor activity (TFA) and TF related antigen (TFR:AG) were determined in an extracellular culture medium of HL-60 cells. After 12 h incubation, TFA and TFR:AG in the medium with endotoxin (EDX: 1 μg/ml) reached maximums which were 1.8 and 2.1 times greater than those in the medium without EDX, respectively. In the leukemic cells of 10 patients with acute nonlymphoid leukemia (ANLL), TFR:AG showed a significant correlation with TFA (p <0.01). On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 9 publications
0
27
0
2
Order By: Relevance
“…[4][5][6] Tumor cells also express TF, where TF is related to the metastatic potential. [7][8][9] Tissue factor is a 263-amino acid lipoprotein with 3 major domains: (1) an amino-terminal extracellular domain, which binds with high affinity to factor VIIa; (2) a transmembrane domain, which anchors TF to the membrane surface; and (3) a cytoplasmic carboxyterminal domain, which presumably is involved in signal transduction. [10][11][12] Binding of plasma factor VIIa to membrane TF anchors the proteolytic complex and results in an approximately 2 ϫ 10 7 -fold increase in the enzymatic activity of factor VIIa toward its natural substrates factor IX and factor X.…”
mentioning
confidence: 99%
“…[4][5][6] Tumor cells also express TF, where TF is related to the metastatic potential. [7][8][9] Tissue factor is a 263-amino acid lipoprotein with 3 major domains: (1) an amino-terminal extracellular domain, which binds with high affinity to factor VIIa; (2) a transmembrane domain, which anchors TF to the membrane surface; and (3) a cytoplasmic carboxyterminal domain, which presumably is involved in signal transduction. [10][11][12] Binding of plasma factor VIIa to membrane TF anchors the proteolytic complex and results in an approximately 2 ϫ 10 7 -fold increase in the enzymatic activity of factor VIIa toward its natural substrates factor IX and factor X.…”
mentioning
confidence: 99%
“…TF is not expressed on the normal peripheral mononuclear cells unless stimulated by endotoxin or other cytokines (Rickles et al, 1995), nor on myeloid precursor cells (Bauer et al, 1989). TF was also detected in the plasma of patients with leukemia (Kubota et al, 1991;Nakasaki et al, 2000a) and in HL-60 culture medium (Kubota et al, 1991). The evidence for TF expression on proliferating leukemic cells identifies leukemia as a potential candidate for TF-targeting therapies.…”
Section: Tf In Leukemiamentioning
confidence: 83%
“…If untreated, death usually occurs within 6 months in most cases. It was reported that TF is expressed on the human leukemic HL-60 (Freeburn et al, 1995;Kubota et al, 1991;Rickles et al, 1995;Tanaka et al, 1989), Molt-4 (Tanaka, 1989), THP-1 (Tanaka, 1989) cell lines , and on leukemic cells from patients with AML (Andoh et al, 1987;Bauer et al, 1989;Nakasaki et al, 2000b;Tanaka et al, 1989;Tanaka and Kishi, 1990;Tanaka and Yamanishi, 1993) and ALL (Kubota et al, 1991;Nakasaki et al, 2000a). TF is not expressed on the normal peripheral mononuclear cells unless stimulated by endotoxin or other cytokines (Rickles et al, 1995), nor on myeloid precursor cells (Bauer et al, 1989).…”
Section: Tf In Leukemiamentioning
confidence: 99%
“…61,62 Thrombin generation after tissue factor expression or cancer procoagulant secretion by blast cells may also contribute to activate endothelial cells. [63][64][65][66][67] Finally, the generation of neutrophil membrane microparticles has been reported to activate endothelial cells. 68 The extent to which these various mechanisms are involved in myeloblast-dependent endothelial cell activation will have to be determined.…”
Section: Discussionmentioning
confidence: 99%